Risk Factors of Disrupted Ectopic Pregnancy in Pregnant Women - Anisa Nur Azizah; Faizah Betty Rahayuningsih (Indonesian Journal of Global Health Research, 2025)
Disrupted ectopic pregnancy is a serious pregnancy complication that threatens the life of both the fetus and the mother, yet there is limited exploration and analysis of the risk factors associated with disrupted ectopic pregnancy. This study aims to identify the risk factors affecting disrupted ectopic pregnancy. Method: This research is a case-control study with an analytical observational design. The sample used secondary data from medical records of 100 pregnant women with disrupted ectopic pregnancy in the case group and 100 pregnant women without disrupted ectopic pregnancy in the control group at Dr. Moewardi Regional Public Hospital from 2020-2025. Data were analyzed using the Chi-Square test to determine the p-value and odds ratio. The p-values for maternal age, gestational age, parity, abortion history, history of disrupted ectopic pregnancy, contraceptive use, and history of reproductive disease are all 0.000 or 0.003 (<0.05), indicating significant associations between these factors and the occurrence of disrupted ectopic pregnancy. There is a significant relationship between maternal age, gestational age, parity, abortion history, history of disrupted ectopic pregnancy, contraceptive use, and history of reproductive diseases in women with disrupted ectopic pregnancy.